Innovative Approaches to Teaching English as a Second Language in the Digital Age (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores innovative methods and technological tools reshaping English as a Second Language (ESL) instruction in the contemporary digital era. Emphasizing the integration of digital resources, blended learning, and interactive platforms, the paper highlights how these approaches enhance learner engagement, motivation, and language proficiency. The discussion includes pedagogical implications and challenges, providing insights for educators aiming to modernize ESL teaching practices.